Effect of Aging Treatments on the Structure, Deformation Response, and R Transformation in Nanocrystalline Ti–50.9 at.% Ni Alloy - Tamara M. Poletika; Svetlana L. Girsova; Sergey M. Bitter; Aleksander I. Lotkov (Metals, 2022)
This paper presents the results of a transmission electron microscope study of the influence of the size, morphology, and spatial distribution of coherent Ti3Ni4 particles on the nature of the R transformation; the morphology of the R phase; and the deformation response depending on the aging temperature in nanocrystalline Ti–50.9 at.% Ni alloy with a grain–subgrain structure. It has been established that with an increase in the aging temperature, the size and spatial distribution of Ti3Ni4 particles change from being located on dislocations at an aging temperature of 300 °C to precipitation at sub-boundaries at an aging temperature of 400 °C, 450 °C. Correspondingly, the morphology of the R phase changes from nanodomain-like to a lamellar self-accommodation structure. Studies have shown that the morphology of the R phase, in turn, affects the deformation response of the material. In the case of lamellar self-accommodation morphology, localized R transformation develops in a Lüders-like manner.